Spider peptide Phα1β induces analgesic effect in a model of cancer pain. Issue 9 (25th June 2013) - Rigo, Flavia Karine; Trevisan, Gabriela; Rosa, Fernanda; Dalmolin, Gerusa D.; Otuki, Michel Fleith; Cueto, Ana Paula; de, Célio José; Romano‐Silva, Marco Aurelio; Cordeiro, Marta do N.; Richardson, Michael; Ferreira, Juliano; Gomez, Marcus V.
<x xml:space="preserve">Abstract</x> The marine snail peptide ziconotide (ω‐conotoxin MVIIA) is used as an analgesic in cancer patients refractory to opioids, but may induce severe adverse effects. Animal venoms represent a rich source of novel drugs, so we investigated the analgesic effects and the side‐effects of spider peptide Phα1β in a model of cancer pain in mice with or without tolerance to morphine analgesia. Cancer pain was induced by the inoculation of melanoma B16‐F10 cells into the hind paw of C57BL/6 mice. After 14 days, painful hypersensitivity was detected and Phα1β or ω‐conotoxin MVIIA (10–100 pmol/site) was intrathecally injected to evaluate the development of antinociception and side‐effects in control and morphine‐tolerant mice. The treatment with Phα1β or ω‐conotoxin MVIIA fully reversed cancer‐related painful hypersensitivity, with long‐lasting results, at effective doses 50% of 48 (32–72) or 33 (21–53) pmol/site, respectively. Phα1β produced only mild adverse effects, whereas ω‐conotoxin MVIIA induced dose‐related side‐effects in mice at analgesic doses (estimated toxic dose 50% of 30 pmol/site). In addition, we observed that Phα1β was capable of controlling cancer‐related pain even in mice tolerant to morphine antinociception (100% of inhibition) and was able to partially restore morphine analgesia in such animals (56 ± 5% of inhibition). In this study, Phα1β was as efficacious as ω‐conotoxin MVIIA in inducing analgesia in a model of cancer pain without producing severe adverse effects or losing efficacy in opioid‐tolerant mice, indicating that Phα1β has a good profile for the treatment of cancer pain in patients.